Implementasi Musik terhadap Nilai-nilai Religius bagi Umat Islam dan Kristen - Rozi, Abdul Fachrur; Wirman, Wirman (Lembaga Yasin AlSys, 2023)
Music comes from the Greek language mousike which is translated into Latin misuca. The noun mousik or the adjective mousikos is formed from the root mousa, the name of a goddess of the arts and sciences in Greek myth. The influence of music on Islam and Christianity, music can motivate people to be more enthusiastic in carrying out activities such as work. Trigger enthusiasm to work harder. Because the message contained in the poetry of religious music makes you think about the life of the world and the hereafter, because in life you have to balance between the two, but if you listen to music too often to forget the time you can neglect the five daily prayers for Muslims. The method used in this thesis is a library method through a phenomenological approach. This thesis explores data from two sources, namely primary and secondary. Primary data are the Bible and Al-Qur'an, while secondary data are articles, books, documents and websites. The aim is to find out about music in Islam and Christianity, the influence of music on religious values and to broaden thinking and to increase understanding of music. The results of this study want to know the implementation of music on Islamic and Christian values. Music is part of the daily life of the desert people which functions as a complement to public meetings. The application of music in Islam as a welcome for pilgrims to the holy house of the Kaaba, as a motivator and spirit for warriors and travelers. The musical instruments used are made of wood with themes such as war, victory, romance and religion and turn the lyrics into songs. Meanwhile, in Christianity, music is one of the tools during worship. The music server must understand well the meaning of the liturgical elements and implement them in the singing of musical accompaniment. Therefore music in Islam is makruh, but it can be haram if it has a bad impact on the listener.